Procrastination Among University Students: Differentiating Severe Cases in Need of Support From Less Severe Cases - Rozental, Alexander; Forsström, David; Hussoon, Ayah; Klingsieck, Katrin B. (Frontiers in Psychology, 2022)
Procrastination refers to voluntarily postponing an intended course of action despite expecting to be worse off for this delay, and students are considered to be especially negatively affected. According to estimates in the literature, at least half of the students believe procrastination impacts their academic achievements and well-being. As of yet, evidence-based ideas on how to differentiate severe from less severe cases of procrastination in this population do not exist, but are important in order to identify those students in need of support. The current study recruited participants from different universities in Sweden to participate in an anonymous online survey investigating self-rated levels of procrastination, impulsivity, perfectionism, anxiety, depression, stress, and quality of life. Furthermore, diagnostic criteria for pathological delay (PDC) as well as self-report items and open-ended questions were used to determine the severity of their procrastination and its associated physical and psychological issues. In total, 732 participants completed the survey. A median-split on the Pure Procrastination Scale (PPS) and the responses to the PDC were used to differentiate two groups; "less severe procrastination" (PPS ≤ 2.99; n = 344; 67.7% female; M age = 30.03; SD age = 9.35), and "severe procrastination" ((PPS ≥ 3.00; n = 388; 66.2% female; M age = 27.76; SD age = 7.08). For participants in the severe group, 96-97% considered procrastination to a problem, compared to 42-48% in the less severe group. The two groups also differed with regard to considering seeking help for procrastination, 35-38% compared to 5-7%. Participants in the severe group also reported more problems of procrastination in different life domains, greater symptoms, and lower quality of life. A thematic analysis of the responses on what physical issues were related to procrastination revealed that these were characterised by stress and anxiety, e.g., tension, pain, and sleep and rest, while the psychological issues were related to stress and anxiety, but also depression, e.g., self-criticism, remorse, and self-esteem. The current study recommends the PPS to be used as an initial screening tool, while the PDC can more accurately determine the severity level of procrastination for a specific individual.